Urolithin Α modulates inter-organellar communication via calcium-dependent mitophagy to promote healthy ageing - Roussos, Antonis; Kitopoulou, Katerina; Fivos Borbolis; Ploumi, Christina; Gianniou, Despoina D.; Li, Zhiquan; He, Haijun; Tsakiri, Eleni; Borland, Helena; Kostakis, Ioannis K.; Samiotaki, Martina; Trougakos, Ioannis P.; et al. (Autophagy, 2025)
Mitochondrial dysfunction and impaired mitophagy are hallmarks of ageing and age-related pathologies. Disrupted inter-organellar communication among mitochondria, endoplasmic reticulum (ER), and lysosomes, further contributes to cellular dysfunction. While mitophagy has emerged as a promising target for neuroprotection and geroprotection, its potential to restore age-associated defects in organellar crosstalk remains unclear. Here, we show that mitophagy deficiency deregulates the morphology and homeostasis of mitochondria, ER and lysosomes, mirroring age-related alterations. In contrast, Urolithin A (UA), a gut-derived metabolite and potent mitophagy inducer, restores inter-organellar communication via calcium signaling, thereby, promoting mitophagy, healthspan and longevity. Our multi-omic analysis reveals that UA reorganizes ER, mitochondrial and lysosomal networks, linking inter-organellar dynamics to mitochondrial quality control. In Caenorhabditis elegans, UA induces calcium release from the ER, enhances lysosomal activity, and drives DRP-1/DNM1L/DRP1-mediated mitochondrial fission, culminating in efficient mitophagy. Calcium chelation abolishes UA-induced mitophagy, blocking its beneficial impact on muscle function and lifespan, underscoring the critical role of calcium signaling in UA's geroprotective effects. Furthermore, UA-induced calcium elevation activates mitochondrial biogenesis via UNC-43/CAMK2D and SKN-1/NFE2L2/Nrf2 pathways, which are both essential for healthspan and lifespan extension. Similarly, in mammalian cells, UA increases intracellular calcium, enhances mitophagy and mitochondrial metabolism, and mitigates stress-induced senescence in a calcium-dependent manner. Our findings uncover a conserved mechanism by which UA-induced mitophagy restores inter-organellar communication, supporting cellular homeostasis and organismal health.Abbreviations: Ca(2+): calcium ions; BJ: human foreskin fibroblasts; BNIP3: BCL2 interacting protein 3; BP: bipyridyl; CAMK2D: calcium/calmodulin dependent protein kinase II delta; CCCP: carbonyl cyanide m-chlorophenyl hydrazone; DEGs: differentially expressed genes; DEPs : differentially expressed peptides; DFP: deferiprone; DNM1L/DRP1: dynamin 1 like; EGTA: ethylene glycol bis(2-aminoethyl ether)-N,N,N',N'-tetraacetic acid; EMC: endoplasmic reticulum membrane protein complex; ER: endoplasmic reticulum; FCCP: carbonyl cyanide p-trifluoro-methoxyphenyl hydrazone; GO: gene ontology; GSVA: Gene Set Variation Analysis; HUVECs: human umbilical vein endothelial cells; IMM: inner mitochondrial membrane; ITPR/InsP3R: inositol 1,4,5-triphosphate receptor; MAM: mitochondria-associated ER membrane; MAPK: mitogen-activated protein kinase; MCU: mitochondrial calcium uniporter; MEFs: mouse embryonic fibroblasts; NAC : N-acetylcysteine; NFE2L2/Nrf2: NFE2 like bZIP transcription factor 2; NMN: nicotinamide mononucleotide; NR: nicotinamide riboside; OMM: outer mitochondrial membrane; PCA: principal-component analysis; PPARGC1A/PGC1α: PPARG coactivator 1 alpha; PQ: paraquat; TMCO: transmembrane and coiled-coil domains 1; TMRE: tetramethylrhodamine ethyl ester perchlorate; UA: urolithin A; VDAC: voltage dependent anion channel.
Keywords: calcium; cellular senescence; ER; geroprotection; Lysosome; Mitochondria